Pengaruh Likuiditas, Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Tekstil Dan Garment Yang Terdaftar Di Bursa Efek Indonesia - Yunita Althin Natanael; Deni Trianda Pitri (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to provide evidence regarding the influence of company liquidity and profitability on stock prices. The financial ratios studied were Liquidity as measured by Current Ratio (CR) and Profitability as measured by Return on Assets (ROA) as the independent variable and stock prices as the dependent variable. The sample used in this study were textile and garment manufacturing companies listed on the IDX that were actively traded from 2017 to 2018. The sampling method used is saturated sampling technique, which is a sampling technique when all members of the population are used as samples. The statistical method used in this research is descriptive and hypothetical. The results of this study indicate that the ratio variables Current Ratio and Return on Assets simultaneously statistically have no significant effect on predicting stock prices that will be traded on the stock exchange Keywords: Current Ratio, Return on Assets, and Stock Prices.